Epistemic Exclusion of Women Faculty and Faculty of Color: Understanding Scholar(ly) Devaluation as a Predictor of Turnover Intentions. (2nd January 2022) - Settles, Isis H.; Jones, Martinque K.; Buchanan, NiCole T.; Brassel, Sheila T.
ABSTRACT: Faculty diversity has received increased attention from researchers and institutions of higher education, yet faculty demographics have not changed substantially for many underrepresented groups. Several barriers to the retention of women and faculty of color have been offered, including a lack of belonging, discrimination, social exclusion, and tokenism. Epistemic exclusion, scholarly marginalization rooted in disciplinary and identity-based biases, is theorized to act as another barrier to the retention of these faculty. The present study examines the effect of scholarly devaluation, a primary component of epistemic exclusion, on faculty workplace outcomes using data from 1, 341 tenure-track faculty from a predominantly White, research-intensive institution. We found that women and underrepresented faculty of color reported higher perceptions of scholarly devaluation. Further, scholarly devaluation was associated with higher intentions to leave the university and this relationship was mediated by lower job satisfaction and poorer perceptions of the workplace climate. Notably, the negative consequences of perceiving scholarly devaluation were found for all faculty, not just women and faculty of color. We discuss the implications of these findings for retaining marginalized faculty and for institutions of higher education more broadly.